2012
DOI: 10.1080/19338244.2011.598888
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Ambient Ozone and PM2.5Levels and Asthma Emergency Department Visits: Possible Influence of Gender and Ethnicity

Abstract: An investigation of the relationship of air pollution and emergency department (ED) visits for asthma was an opportunity to assess environmental risks for asthma exacerbations in an urban population. A total of 6,979 individuals with a primary discharge diagnosis of asthma presented to 1 of 6 EDs in the Pittsburgh, Pennsylvania, area between 2002 and 2005. Using a case-crossover methodology, which controls for the effects of subject-specific covariates such as gender and race, a 2.5% increase was observed in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 16 publications
2
30
1
Order By: Relevance
“…In the case study, for the regions where the futureyear annual PM 2.5 concentration is far below the NAAQS ( < 7.2 μg$m -3 ) (e.g., West Virginia, Virginia) and the ratio is low, the emission reduction rate can be cut down. Instead, for the nonattainment state with high ratio (e.g., California), the emission reduction rate should be increased in main sources (local or regional) to achieve Abbey et al [32] acute myocardial infarction, non-fatal 18 99 Zanobetti et al [25] asthma emergency room visits 0 99 pooled estimate b) : Slaughter et al [33] Mar et al [34] Glad et al [35] acute bronchitis 8 12 Dockery et al [36] willing to pay asthma exacerbation 6 18 Ostro et al [37] acute respiratory symptoms 18 64 Ostro and Rothschild [38] Notes: a) the valuation methods are selected from BenMAP-CE database depends on the health endpoint and its age range; b) the pooling method is "fixed effects" both the targeted air quality and large increase in health and economic benefits. Besides, regions with high ratio (e.g., California, Texas) would suggest higher priority in the implementation of the control strategy.…”
Section: Case Studymentioning
confidence: 98%
“…In the case study, for the regions where the futureyear annual PM 2.5 concentration is far below the NAAQS ( < 7.2 μg$m -3 ) (e.g., West Virginia, Virginia) and the ratio is low, the emission reduction rate can be cut down. Instead, for the nonattainment state with high ratio (e.g., California), the emission reduction rate should be increased in main sources (local or regional) to achieve Abbey et al [32] acute myocardial infarction, non-fatal 18 99 Zanobetti et al [25] asthma emergency room visits 0 99 pooled estimate b) : Slaughter et al [33] Mar et al [34] Glad et al [35] acute bronchitis 8 12 Dockery et al [36] willing to pay asthma exacerbation 6 18 Ostro et al [37] acute respiratory symptoms 18 64 Ostro and Rothschild [38] Notes: a) the valuation methods are selected from BenMAP-CE database depends on the health endpoint and its age range; b) the pooling method is "fixed effects" both the targeted air quality and large increase in health and economic benefits. Besides, regions with high ratio (e.g., California, Texas) would suggest higher priority in the implementation of the control strategy.…”
Section: Case Studymentioning
confidence: 98%
“…However, most air pollution epidemiology studies do not have this information, and instead use stationary ambient monitors to measure the concentrations of air pollutants to which nearby (and not so nearby) populations may be exposed [16,18,19,21,26,27]. These studies then assume that the measurements from these monitoring stations are reasonable approximations of what a nearby resident inhales.…”
Section: Assessment Of Health Effect Outcomes Attributed To Ozonementioning
confidence: 99%
“…The EPA Administrator placed the most weight on human controlled exposure studies for the 2015 ozone review, and these studies formed the basis for the EPA’s choice of standard levels [14,15]. A large literature of epidemiology studies also exists that investigate the associations between health effects in populations and ambient ozone concentrations [16,17,18,19,20,21,22,23]. These studies are useful, but can only provide information about correlation between ozone and health effects, not causation [24].…”
Section: Introductionmentioning
confidence: 99%
“…Because ozone is a respiratory irritant that causes bronchial inflammation and hyperresponsiveness (16,17), people with preexisting obstructive lung disease are particularly susceptible to adverse respiratory effects of ozone. A substantial body of evidence has shown that modest short-term increases in ground-level ozone increase risk of acute care visits and hospitalization for asthma (18)(19)(20)(21) and COPD (22,23). Ozone exposure has been associated with deterioration in asthma control in studies in the United States and Europe, resulting in increased medication use and missed school and work days (24)(25)(26).…”
Section: Environmental Air Pollution and Climate Changementioning
confidence: 99%